Implementation of Clean and Healthy Living Behaviors in Early Childhood - Madong, Salma; Herlina, Herlina; Bachtiar, Muhammad Yusri; Wahira, Wahira (Journal of Health Science and Medical Therapy, 2025)
PHBS activities made for early childhood are activities to foster and develop healthy living habits and behaviours in students, which are carried out comprehensively and integrated; for that, for the activity to take place well, it is necessary to plan, implement and evaluate an activity carried out to students to achieve the desired goals. This study aims to provide an overview of implementing clean and healthy living behaviours in children. This qualitative research is descriptive, which is a type of research that describes a symptom, condition, and existing situation. Data collection techniques are carried out through observation, interviews and documentation. The results of this study include efforts made to habituate clean and healthy living behaviours in children by providing their activities, such as washing their hands and taking out garbage. The supporting factors for implementing clean and healthy living behaviours in early childhood are rules and regulations at school that support clean and healthy living behaviour activities, parents, and the family environment. The earliest place is the family environment for implementing clean and healthy living behaviours and peers, which is usually when there are students who do activities, other students tend to do it too.